(untitled) (Innovation & Development in Engineering and Applied Science, 2021)
The objective of the project is to make a video game, adapting an electronic system in the arm to a patient with hemiparesis, and thus stimulate the fine motor in its left upper extremity contributing to its rehabilitation. Several experiments were carried out taking operational data such as the number of player points obtained in several tests and performing the analysis of movement in the affected limb in both arm and wrist. As a result we can observe the work done by the left arm that is the objective of the project. The video game being friendly for the fantasy environment, encourages the interest of the patient, making him like to play with the system, thus obtaining a taste for moving the affected arm, thus creating new neuronal pathways for movement and stimulation of their motor skills fine.